The epistemological function of hermeneutics in African philosophy. The case of Basil-Juléat Fouda - (:unkn) unknown (My University, 2024)
The aim of this article is to examine the philosophical legitimacy of the work of Basil-Juléat Fouda, a philosopher whose thought has marked and continues to mark philosophical discussion in Africa. So as not to embrace all the possibilities open to us in this undertaking at once, the following discussion will highlight the epistemological function of hermeneutics in this offer. B.-J. Fouda insists on the way in which African or Negro philosophy must be interpreted. For him, it is through hermeneutics that it must be understood. We intend to apply this insight to his own philosophical analysis in order to bring out this epistemological function of hermeneutics. To do this, we will focus on the relationship between B.-J. Fouda’s thoughts and the theory of philosophical hermeneutics as epistemology. The truth is that B.-J. Fouda’s Negro-African philosophy of existence can be understood in abstraction from the essentially critical demands of modern philosophy, but its epistemological contribution can be measured in terms of a global or totalising conception of philosophical wisdom, as reflected in hermeneutic philosophy. Furthermore, the outline and choice of a hermeneutic epistemology is, in our opinion, the most appropriate if we wish to understand the reason for the distance that separates Macien Towa and Basil-Juléat Fouda.
Keywords: African Research